Cargo and cell‐specific differences in extracellular vesicle populations identified by multiplexed immunofluorescent analysis. Issue 1 (17th July 2020) - Burbidge, Kevin; Zwikelmaier, Virginia; Cook, Ben; Long, Michael M.; Balva, Barak; Lonigro, Michael; Ispas, Grace; Rademacher, David J.; Campbell, Edward M.
ABSTRACT: Extracellular vesicles (EVs) have been implicated in a wide variety of biological activities, have been implicated in the pathogenesis of numerous diseases, and have been proposed to serve as potential biomarkers of disease in human patients and animal models. However, characterization of EV populations is often performed using methods that do not account for the heterogeneity of EV populations and require comparatively large sample sizes to facilitate analysis. Here, we describe an imaging‐based method that allows for the multiplexed characterization of EV populations at the single EV level following centrifugation of EV populations directly onto cover slips, allowing comprehensive analysis of EV populations with relatively small samples. We observe that canonical EV markers are present on subsets of EVs which differ substantially in a producer cell and cargo specific fashion, including differences in EVs containing different HIV‐1 proteins previously reported to be incorporated into pathogenic EVs. We also describe a lectin binding assay to interrogate EVs based on their glycan content, which we observe to change in response to pharmacological modulation of secretory autophagy pathways. These studies collectively reveal that a multiplexed analysis of EV populations using fluorescent microscopy can reveal differences in specific EV populations that may be used to understand the biogenesis of specific EV populations and/or to interrogate small subsets of EVs of interest within larger EV populations in biological samples.